2020
DOI: 10.30659/jai.9.1.37-51
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kualitas Komite Audit dan Ukuran Kantor Akuntan Publik terhadap Manajemen Laba

Abstract: This study aims to determine the effect of the quality of the audit committee and the size of the public accounting firm on earnings management. The audit committee uses the proxy size of the audit committee, the number of audit committee meetings, the independent audit committee and the expertise of the audit committee. This study uses secondary data, namely companies in the category of basic industrial and chemical manufacturing sectors listed on the Indonesia Stock Exchange (IDX). The sample used 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
0
0
4

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 6 publications
5
0
0
4
Order By: Relevance
“…This was proven by the coefficient value of -3.286184 (-328%), indicating that when the number of independent commissioners increases, it will reduce earnings management carried out by companies that, on average, engage in positive earnings management. These findings align with research (Alfiyasahra & Challen, 2020;Handriani, 2020) but oppose the research results of (Arifin & Destriana, 2016).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…This was proven by the coefficient value of -3.286184 (-328%), indicating that when the number of independent commissioners increases, it will reduce earnings management carried out by companies that, on average, engage in positive earnings management. These findings align with research (Alfiyasahra & Challen, 2020;Handriani, 2020) but oppose the research results of (Arifin & Destriana, 2016).…”
Section: Discussionsupporting
confidence: 84%
“…From the results of the review, it can produce a report that the principal will later use for company decision-making. These results corroborate with research conducted by Alfiyasahra and Challen (2020). this differs from previous research conducted by Handriani (2020), which revealed that independent audit committees did not affect earnings management.…”
Section: Descriptive Statisticssupporting
confidence: 89%
See 3 more Smart Citations